KARAKTERISTIK METASTASIS SISTEM SARAF PUSAT DARI KANKER PARU - Tan Yosephine*, Tiara Aninditha**, Henry Riyanto Sofyan**, Jonathan Odilo***, Rini Andriani**** (NEURONA, 2020)
INTRODUCTION A S MUCH AS 40 OF LUNG CANCER PATIENTS WILL EXPERIENCE CENTRAL NERVOUS SYSTEM CNS METASTASIS IN THE COURSE OF THE DISEASE FROM THOSE 40 AS MUCH AS 39 WILL EXPERIENCE LEPTOMENINGEAL METASTASIS BUT THE CLINICAL PROFILE OF CNS INVOLVEMENT IN LUNG CANCER HAS NEVER BEEN STUDIED BEFORE IN INDONESIA